Band structure of Ge1−xSnx alloy: a full-zone 30-band k · p model. (23rd July 2019) - Song, Zhigang; Fan, Weijun; Tan, Chuan Seng; Wang, Qijie; Nam, Donguk; Zhang, Dao Hua; Sun, Greg
Abstract: A full-zone 30-band k · p model is developed as an efficient and reliable tool to compute electronic band structure in Ge1− x Sn x alloy. The model was first used to reproduce the electronic band structures in Ge and α -Sn obtained with empirical tight binding and ab initio methods. Input parameters for the 30-band k · p model are carefully calibrated against prior empirical predications and experimental data. Important material properties such as effective mass for electrons and holes, Luttinger parameters, and density of states are obtained for Ge1− x Sn x alloy with the composition range 0 <  x  < 0.3. The 30-band k  ·  p model that requires far less computing resources is a necessary capability for optimization of sophisticated devices made from Ge1− x Sn x alloy with a large parameter space to explore.